Current state of clinical ultrasound neuromodulation - Matt, Eva; Radjenovic, Sonja; Mitterwallner, Michael; Beisteiner, Roland (Frontiers in Neuroscience, 2024)
Unmatched by other non-invasive brain stimulation techniques, transcranial ultrasound (TUS) offers highly focal stimulation not only on the cortical surface but also in deep brain structures. These unique attributes are invaluable in both basic and clinical research and might open new avenues for treating neurological and psychiatric diseases. Here, we provide a concise overview of the expanding volume of clinical investigations in recent years and upcoming research initiatives concerning focused ultrasound neuromodulation.Currently, clinical TUS research addresses a variety of neuropsychiatric conditions, such as pain, dementia, movement disorders, psychiatric conditions, epilepsy, disorders of consciousness, and developmental disorders. As demonstrated in sham-controlled randomized studies, TUS neuromodulation improved cognitive functions and mood, and alleviated symptoms in schizophrenia and autism. Further, preliminary uncontrolled evidence suggests relieved anxiety, enhanced motor functions in movement disorders, reduced epileptic seizure frequency, improved responsiveness in patients with minimally conscious state, as well as pain reduction after neuromodulatory TUS.While constrained by the relatively modest number of investigations, primarily consisting of uncontrolled feasibility trials with small sample sizes, TUS holds encouraging prospects for treating neuropsychiatric disorders. Larger sham-controlled randomized trials, alongside further basic research into the mechanisms of action and optimal sonication parameters, are inevitably needed to unfold the full potential of TUS neuromodulation.